Is physiotherapy effective in the management of child and adolescent conversion disorder? A systematic review. (13th June 2014) - FitzGerald, Tara L; Southby, Alesha K; Haines, Terrence P; Hough, Janet P; Skinner, Elizabeth H
Abstract Child and adolescent conversion disorder has the potential to impart significant burden on health‐care services and affect quality of life. Clinically, physiotherapists are involved in conversion disorder management; however, no systematic reviews have examined physiotherapy effectiveness in its management. The aim of this review is to identify the efficacy of physiotherapy management of child and adolescent conversion disorder. A search of multiple databases (Medline, CINAHL, Embase, PsychINFO, PEDro and the Cochrane Library) was completed along with manual searching of relevant reference lists to identify articles including children 0–18 years with a diagnosis of conversion disorder who received physical management. Two independent reviewers screened titles and abstracts using criteria. Data were extracted regarding study characteristics, functional outcome measures, length of stay, physiotherapy service duration and resolution of conversion symptoms. Methodological quality was assessed using a tool designed for observational studies. Twelve observational studies were included. No functional outcome measures were used to assess the effectiveness of the treatment protocols in the case studies. Resolution of symptoms occurred in all but two cases, with conversion symptoms still present at 11 months and at 2 years. Length of stay varied from 3 days to 16 weeks, with similar variation evident in length of physiotherapy service provision (2.5 weeks to 16 weeks). There was limited and poor quality evidence to establish the efficacy of physiotherapy management of child and adolescent conversion disorders. More rigorous study designs with consistent use of reliable, valid and sensitive functional outcome measures are needed in this area.